2022
DOI: 10.3390/biomedicines10030573
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Directions of Immunotherapies in Soft Tissue Sarcomas

Abstract: Immunotherapy in soft tissue sarcoma (STS) has experienced a surge of interest in the past decade, contributing to an expanding number of therapeutic options for this extremely heterogenous group of rare malignancies. Immune checkpoint inhibitors (CPIs) targeting the PD-1 and CTLA-4 axes have demonstrated promising responses in a select number of STS subtypes, including rarer subtypes, such as alveolar soft part sarcoma, SWI/SNF-deficient sarcomas, clear cell sarcoma, and angiosarcoma. Multiple pan-subtype sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 146 publications
0
11
0
Order By: Relevance
“… 79 , 80 Promising findings regarding immune checkpoint inhibitors would also suggest a role for immunotherapy (PD1/PDL1 inhibitors) administered within clinical trials (if available) or on compassionate grounds. 81–84 …”
Section: Treatment Recommendations Specific To Certain Adult-type Nrstsmentioning
confidence: 99%
See 1 more Smart Citation
“… 79 , 80 Promising findings regarding immune checkpoint inhibitors would also suggest a role for immunotherapy (PD1/PDL1 inhibitors) administered within clinical trials (if available) or on compassionate grounds. 81–84 …”
Section: Treatment Recommendations Specific To Certain Adult-type Nrstsmentioning
confidence: 99%
“…79,80 Promising findings regarding immune checkpoint inhibitors would also suggest a role for immunotherapy (PD1/PDL1 inhibitors) administered within clinical trials (if available) or on compassionate grounds. [81][82][83][84] Clear Cell Sarcoma CCS of tendons and aponeuroses is extremely rare in childhood and little information is available on its clinical behaviour in pediatric age. 35 It is generally described as a very aggressive tumor with a very limited responsiveness to standard chemotherapy.…”
Section: Alveolar Soft Part Sarcomamentioning
confidence: 99%
“…Nevertheless, a subset of patients showed remarkable and durable responses, after the failure of many traditional systemic treatments. Furthermore, recent research has restored hope in the possibility of sarcomas being treatable by immunotherapy [ 76 ]. One of the major challenges is to define the best candidates for these treatments by a better knowledge of each tumor’s immune component’s microenvironment and by the use of reliable biomarkers and response predictors, in order to optimize personalized medicine plans.…”
Section: Discussionmentioning
confidence: 99%
“…Trabectedin selectively reduces monocytes and TAMs in treated tumors and can increase the presence and functional activity of T lymphocytes. In fibrosarcoma models with poor response to PD-1 immunotherapy, treatment with Trabectedin prior to anti-PD-1 can improve antitumor efficacy ( 77 , 78 ). In addition, an earlier study showed that the chemotherapy drug decitabine facilitates immune recognition of sarcoma cells by upregulating cancer/testis antigens, MHC molecules, and intracellular cell adhesion molecule-1 ( 79 ).…”
Section: Research Evidence In Sarcomasmentioning
confidence: 99%